2014
DOI: 10.1063/1.4865618
|View full text |Cite
|
Sign up to set email alerts
|

Formation and annealing of boron-oxygen defects in irradiated silicon and silicon-germanium n+–p structures

Abstract: New findings on the formation and annealing of interstitial boron-interstitial oxygen complex (B i O i ) in ptype silicon are presented. Different types of n+-p structures irradiated with electrons and alpha-particles have been used for DLTS and MCTS studies. Electronic excitation essentially changes the formation rate of B i O i . It has been found that the increase of oxygen content slows the B i O i annealing rate down. The activation energy of the B i O i dissociation has been determined and it was found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 7 publications
2
12
0
Order By: Relevance
“…) consistent with the results of Refs. . Thus, the presently reported FCE annealing procedure leads to a significant decrease in the activation energy for the annealing of the B i O i complex (Δ E a ∼1 eV), similar to the case of interstitial aluminum and boron in silicon .…”
Section: Annealing Studiessupporting
confidence: 64%
See 1 more Smart Citation
“…) consistent with the results of Refs. . Thus, the presently reported FCE annealing procedure leads to a significant decrease in the activation energy for the annealing of the B i O i complex (Δ E a ∼1 eV), similar to the case of interstitial aluminum and boron in silicon .…”
Section: Annealing Studiessupporting
confidence: 64%
“… to be E a = 1.2 eV. However, more recent studies reported slightly higher values E a = 1.35–1.4 eV. The annealing rate increases with the increase of the boron concentration and the decrease of oxygen content .…”
Section: Introductionmentioning
confidence: 79%
“…In the previous studies , it was shown by DLTS that the B i C s complexes in boron‐doped Cz‐Si arise synchronously with the dissociation of B i O i defects. The annealing temperature for B i O i , according to the studies is 150–200 °C, i.e., slightly higher than that for B i B s defects observed by us. Taking into account the closeness of these two annealing processes, it can be concluded that B i atoms liberated as a result of the dissociation of both B i B s and B i O i are involved in the formation of B i C s defects in the oxygen‐rich material.…”
Section: Resultsmentioning
confidence: 94%
“…The investigations of the boron‐related radiation defects in Si have been done in the main by deep level transient spectroscopy (DLTS) and electron paramagnetic resonance (EPR) . The main defect appearing in boron‐doped Si under the irradiation is known to be interstitial boron (B i ), which is created through the interaction of a self‐interstitial atom (I) with substitutional boron .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation